Panda kindergarten - Ryder, Joanne; Feng, Katherine (New York : Collins, 2009)
Photographs and text follow sixteen panda cubs at the Wolong Nature Preserve, where they are raised and observed by scientists and workers while they learn survival skills that will allow them to be re-released into the wild.
Booklist
New York Times
School Library Journal
Booklist, June 2009
Bulletin (Center for Children's books), September 2009
Horn Book, April 2010
Keywords: Giant panda -- Anecdotes -- Juvenile literature; Giant panda; Pandas; Giant pandas; Pandas